Margaret Storm Jameson : a Life. - Birkett, Jennifer (Oxford University Press, 2009)
The life-story of Margaret Storm Jameson (1891-1986), prolific novelist and political activist. In her time Jameson gained international recognition for her writing and for her wartime work as President of PEN, fighting for freedom and social justice while rescuing refugees from Nazi Europe and British internment camps. - ;From her childhood in Whitby to her long old age in Cambridge, the life of Margaret Storm Jameson (1891-1986), novelist, autobiographer, and political activist, spanned almost the whole of the twentieth century. A self-styled Little Englander by nature, and European by nurtu.